SCIENTIFIC-PEDAGOGICAL ASPECT AND STRUCTURE OF THE CONCEPT OF SPEECH COMPETENCE (International journal of artificial intelligence, 2026)
This article will highlight the scientific and pedagogical essence of the concept of speech competence, its structural structure and its role in the educational process. The theoretical foundations of competence are analyzed, in particular, in relation to linguistics and psycholinguistics, and the importance of the competency approach in improving educational efficiency is substantiated.